PENEROBOSAN DAN PERUSAKAN GEDUNG KONSULAT AMERIKA SERIKAT DI BENGHAZI, LIBYA DITINJAU DARI HUKUM DIPLOMATIK - Novi Monalisa Anastasia Tambun; Sutiarnoto Sutiarnoto; Arif Arif (Journal of USU International Law, 2013)
Abstraction There is no one state can detach from other states. Because of the interest of a state in another state, it was created a relations. Therefore, diplomatic representatives is to establish friendly relations and enhance cooperation between the two states. Currently, there are still many violent acts that threaten the safety of diplomats in diplomatic duties. . As in the case of Intrusion and Damage Againts the US Consulate in Benghazi, Libya. The question are, How the case is going on ? How does the handling or settlement of the case? The research method to write this journal used was the library research. Selecting and collecting data from a variety of books, doctrins, dictionary, encyclopedia, international law literature, or international politic relations that related with this journal.